CAREC 2030 connecting the region for shared and sustainable development. (Metro Manila, Philippines Asian Development Bank, 2017)
The CAREC Program, now 16 years in operation, has recorded impressive achievements in regional economic cooperation, particularly in the areas of transport, energy, trade facilitation, and trade policy. From 2001 to end September 2017, investments in member countries under CAREC have amounted to 30.5 billion dollar, covering 182 projects. CAREC 2030 builds on the solid foundation of progress made under CAREC 2020, and provides the new long term strategic framework for the CAREC Program leading to 2030. CAREC 2030 is aligned with national strategies and with the 2030 global development agenda. It is inspired by a mission to create an open and inclusive platform that connects people, policies and projects for shared and sustainable development.
Keywords: Central Asia -- Economic integrtion; Electronic books